Students' experiences of embedded academic literacy support in a graduate entry nursing program: A qualitative study. (January 2018) - Ramjan, Lucie M.; Maneze, Della; Everett, Bronwyn; Glew, Paul; Trajkovski, Suza; Lynch, Joan; Salamonson, Yenna
Abstract: Graduate entry nursing (GEN) programs were designed to address the predicted nursing shortfall. In Australia, although these programs attract students from culturally and linguistically diverse (CALD) backgrounds, the workload is compounded by cultural differences and a new academic learning environment which presents additional challenges. This qualitative descriptive study explored the experiences of GEN students enrolled in the introductory unit of their nursing program with embedded academic literacy support in Sydney, Australia. Twenty-four commencing GEN students were interviewed in January 2016. Interviews were transcribed verbatim and thematically analysed. Three main themes emerged which illustrated that GEN students were 'diamonds in the rough'. They possessed a raw natural beauty that required some shaping and polishing to ensure academic needs were met. To ensure retention is high, institutions need to evaluate how best to support and harness the potential of these unique students. Highlights: GEN students bring critical thinking to academia from life experience. CALD GEN students may need to improve academic literacy and oral communication skills. Embedded literacy support ensures successful GEN student transition.